2022
DOI: 10.47391/jpma.3890
|View full text |Cite
|
Sign up to set email alerts
|

Verona integron encoded metallo Beta lactamase (VIM) and Vietnam extended spectrum Beta lactamase (VEB) producing Pseudomonas balearica from a clinical specimen

Abstract: Pseudomonas balearica, a saprophyte found in marshy and marine habitats, is not routinely differentiated from P. aeruginosa and P. stutzeri using automated systems and hence has not been reported from clinical samples. This study describes the identification of P. balearica using MALDI-TOF-MS and 16S rDNA sequence from a patient admitted to an intensive care unit (I.C.U.). The isolate was found to be Verona integron-mediated Metallo-Beta-lactamase (V.I.M.), and Vietnam extended-spectrum Beta-lactamase (V.E.B.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Meanwhile, 13 strains were associated with plants, one with fungal spores, seven with animals and, interestingly, three were derived from human samples, one from the skin of a healthy individual and two from clinical samples. Indeed, a recent study reported a clinical carbapenem-resistant S. balearica strain isolated from a tracheal aspirate and carrying a VIM metallo-β-lactamase ( Uddin et al, 2022 ). This suggests that potential of S. balearica to cause opportunistic infections and to carry relevant antimicrobial-resistance factors should not be disregarded, especially considering that rapid phenotypic identification methods often misidentify S. balearica strains as S. stutzeri ( Uddin et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, 13 strains were associated with plants, one with fungal spores, seven with animals and, interestingly, three were derived from human samples, one from the skin of a healthy individual and two from clinical samples. Indeed, a recent study reported a clinical carbapenem-resistant S. balearica strain isolated from a tracheal aspirate and carrying a VIM metallo-β-lactamase ( Uddin et al, 2022 ). This suggests that potential of S. balearica to cause opportunistic infections and to carry relevant antimicrobial-resistance factors should not be disregarded, especially considering that rapid phenotypic identification methods often misidentify S. balearica strains as S. stutzeri ( Uddin et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent study reported a clinical carbapenem-resistant S. balearica strain isolated from a tracheal aspirate and carrying a VIM metallo-β-lactamase ( Uddin et al, 2022 ). This suggests that potential of S. balearica to cause opportunistic infections and to carry relevant antimicrobial-resistance factors should not be disregarded, especially considering that rapid phenotypic identification methods often misidentify S. balearica strains as S. stutzeri ( Uddin et al, 2022 ). Indeed, S. stutzeri is often isolated from clinical samples ( Köse et al, 2004 ; Sader and Jones, 2005 ; Scotta et al, 2012 ; Mulet et al, 2017 ), which highlights the importance of accurate species and phylogenomic species identification in the clinics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations